الحراك المهني وتفضيلات العودة الطوعية وإعادة التوطين: دراسة تتبعية لعينة من العمالة السورية اللاجئة بالمجتمع المصري - هندي، عبدالمجيد أحمد (جامعة القاهرة - كلية الآداب - مركز البحوث والدراسات الاجتماعية, 2024)
استهدفت الدراسة تتبع أوضاع اللاجئين من خلال الوقوف على حالة الحراك المهني، وتوصيف أبرز الجوانب التي من شأنها التأثير في تفضيلات العودة الطوعية، أو إعادة التوطين لبلد ثالث لدى العمالة السورية اللاجئة بمصر، وقد أسست الدراسة على تساؤلات عدة منها، ما أوجه التأثير الإيجابي والسلبى للحراك المهني في تفضيلات العودة الطوعية للموطن الأصلي أو إعادة التوطين، وإلى أي مدى يؤثر الاندماج الاقتصادي والاجتماعي للعمالة السورية في حالة الحراك المهني لديهم، وهل لمدة الإقامة بالمجتمع المضيف تأثيرا سواء في الحراك المهني أو في تفضيلات العودة أو إعادة التوطين. اتخذت الدراسة من نظريات الاختيار العقلاني والاستيعاب المجزأ ونموذج الاستيعاب موجها نظريا، واعتمدت منهجيا على طريقة منهج المسح الاجتماعي بالعينة، وصحيفة الاستبيان الإلكتروني كأداة لجمع البيانات، وطبقت الدراسة على عينة عشوائية بسيطة من العمالة السورية اللاجئة قوامها (٤٨٩) مفردة، وأوضحت النتائج العامة أن غالبية من حققوا حراكا صاعدا لا يرغبون في العودة للموطن الأصلي أو إعادة التوطين إلى بلد ثالث، وفي المقابل فإن غالبية ذوى الحراك الهابط يرغبون في إعادة التوطين ثم العودة للموطن الأصلي، وكلما اتجه الحراك المهني رأسيا لأعلى، زاد التوجه نحو عدم الموافقة على العودة الطوعية أو إعادة التوطين، وأن الاندماج الاقتصادي والاجتماعي يمثلان العامل المؤثر في تحقيق الحراك المهني الصاعد، وأن من حققوا حراكًا مهنيًا صاعدًا قد أمضوا أكثر من نصف عقد من الزمن على الأقل بالمجتمع المضيف، وبالمقارنة تنخفض سنوات الإقامة لذوي الحراك الهابط، أخيرًا تتزايد نسب عدم الموافقة على العودة أو الانتقال لموطن آخر كلما زادت مدة الإقامة بالمجتمع المضيف. The study aims to follow-up the situation of refugees by examining the state of professional mobility and describing the most important aspects influencing the preferences of voluntary repatriation or resettlement to a third country among Syrian refugee workers in Egypt. The study was based on several questions, including: What are the aspects of the positive and negative impact of professional mobility on preferences for voluntary repatriation to the original country or resettlement, What is the extent of the impact of the economic and social integration of Syrian workers on their professional mobility, does the duration of residence in the host country have any effect on occupational mobility or preferences for repatriation or resettlement. The study took the theories of rational choice, Segmented assimilation and the Assimilation model as a theoretical guide. Methodologically, the study used the sample social survey method, and the electronic questionnaire sheet as a data collection tool. The study was applied to a simple random sample of Syrian refugee workers consisting of (489) individuals, the general results showed that the majority of those who achieved upward mobility do not wish to return to the country of origin or resettlement to a third country. On the other hand, the majority of those with downward mobility wish to resettle and then return to the country of origin, The higher the occupational mobility tends vertically, the greater the tendency towards not favoring voluntary return or resettlement, and that socioeconomic integration represent the influencing factor in achieving upward professional mobility, and that those who achieved upward mobility have spent at least half a decade in the host country, and in comparison, the years of residence decrease for those with downward mobility. Finally, the rates of refusal to return or resettle to another country increase, the longer the period of living in the host society.
Keywords: الحراك المهني -- اللاجئون السوريون -- العمالة الأجنبية -- مصر